The Influence of Product Completeness and Prices on Purchasing Decisions at Khiara Electronic Shop of West Seluma Sub-District - Popi Yulanda; Sri Handayani; Suswati Nasution (Journal of Indonesian Management, 2021)
The purpose of this study is to determine the influence of product completeness and price on purchasing decisions at Khiara Electronics Shop, West Seluma Sub-District. The sample in this study were 120 customers who made purchases at Khiara Electronics Shop, West Seluma Sub-District. The data collection used is a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The results of the regression analysis showed that Y = 9.338+ 0.308X1+ 0.477 X2+ e, this illustrates a positive direction of regression, meaning that there is a positive influence between X1 (product completeness) and X2 (price) on purchasing decisions (Y). Product completeness has a significant influence on purchasing decisions at Khiara Electronics Shop, West Seluma Sub-District. This is evidenced by a significant value of 0.000 is less than 0.05. Price has a significant influence on purchasing decisions at Khiara Electronics Shop, West Seluma Sub-District, this is evidenced by a significant value of 0.000 is less than 0.05. Product completeness and price simultaneously have a significant influence on purchasing decisions at Khiara Electronics Shop, West Seluma Sub-District, this is evidenced by a significant value of 0.000 is less than 0.05.